From Zero to AI: Educational Initiatives Through Webinars and Workshops on Developing Machine Learning Models Using TensorFlow - Haq, Hafizh Umar; Mirza Sutrisno; Popy Meilina; Yana Adharani; Nurvelly Rosanti; Jumail; Kevin Arya Dandy; Muhammad Imam Najib; Anggi Rahmadillah; Miftahul Jannah; Rully Mujiastuti (Edumedia Solution, 2026)
The development of Artificial Intelligence (AI) and Machine Learning (ML) requires improved technological literacy and a basic understanding of practical applications. This study aims to introduce the concepts of AI and ML through the implementation of simple machine learning models using TensorFlow. The methods used include material delivery, model implementation practice, and evaluation through pre-tests, post-tests, and feedback questionnaires. The evaluation results show an increase in participants' understanding, marked by an increase in the average score from 76.76 on the pre-test to 80.91 on the post-test, or an increase of 5.41%. In addition, the feedback results showed a very high level of satisfaction, with 96% of participants giving positive ratings. This shows that the TensorFlow-based learning approach is effective in improving basic understanding and skills related to AI and ML.